Corporate income taxation of multinationals and unemployment - Thomas Eichner; Marco Runkel (Center for Economic Studies and ifo Institute (CESifo), 2006)
Within a two-country model with involuntary unemployment, this paper investigates corporate income taxation under separate accounting versus formula apportionment. In contrast to separate accounting, under formula apportionment the corporate tax policy causes a fiscal externality which goes back to unemployment. This unemployment externality is the lowest when the apportionment formula does not contain a payroll factor. It tends to compensate other externalities such that tax rates become inefficiently low. In an empirical calibration, we show that the transition from separate accounting to formula apportionment improves welfare and reduces unemployment. The welfare increase is the strongest under a pure sales formula.
Keywords: H25; H71; J60; 330